TINJAUAN HUKUM TERHADAP KERJASAMA INTERNASIONAL DALAM PEMBAYARAN LINTAS NEGARA BERBASIS KODE QUICK RESPONSE - Tomayahu, Nova Septiani; Gumanti, Retna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
This study aims to analyze the law relating to the use of digitalization in cross-border payment transaction activities using a Quick Response (QR) code. The research method used is a normative juridical research method that takes and processes primary data sources in the form of Bank Indonesia regulations related to the implementation of the Quick Response Code Indonesian Standard (QRIS). The result of this research is that payment transactions using QR codes have been given a legal umbrella and even encourage the public (users) and sellers (merchants) to use them based on Board of Governors Member Regulation Number 21/18/PADG/2019 concerning the Implementation of the Quick Response Code National Standard. The use of QRIS in Indonesia is performed by scanning, which can be performed in two ways: with Merchant Presented Mode (MPM) and Customer Presented Mode (CPM). The enactment of provisions on the implementation of QRIS that can be used in payment transactions outside the territory of Indonesia is also closely related to PBI No.23/7/PBI/2021, concerning Payment System Infrastructure Operators. International cooperation for cross-border payments based on QR codes implemented by Bank Indonesia is the interconnection of payment transactions at merchants between Indonesia (QRIS) and Thailand (Thai QR Codes), and international cooperation between Indonesia (QRIS) and Malaysia (DuitNow QR Code). The institution in charge of processing payment transaction data domestically for the interconnection and interoperability of international cooperation is a switching institution.